Development of an analysis capacity model for high electron mobility transistor AlGaN/GaN - Farti, Azzeddine; Touhami, Abdelkader (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In this paper, we demonstrate the analytical model developed to characterize the gate-to-drain capacitance Cgd and the gate-to-source capacitance Cgs, and the impact of the gate length on those capacitances, for the high electronic mobility transistor based on GaN. This model is developed from our previous work on the current voltage characteristic (I, V), and small signal parameters for AlGaN/GaN HEMT. The research study examined the impact of parasitic resistances (drain, source), low field mobility, the aluminum amount in the AlGaN barrier, and high-speed saturation. The developed model has matched the experimental data well, confirming the validity, accuracy, and robustness of the model we have developed.